Ten Years Back, Five Years Forward: The Data Seal of Approval - Ingrid Dillo; Lisa de Leeuw (International Journal of Digital Curation, 2015)
If we want to share data, the long-term storage of those data in a trustworthy digital archive is an essential condition. Trust is the basis of storing and sharing data. That trust must be present in the various stakeholders involved. Certification of digital archives can make an important contribution to the confidence of these stakeholders in the digital archives.